Radioactivity and the environment: technical approaches to understand the role of arbuscular mycorrhizal plants in radionuclide bioaccumulation - Davies, Helena S.; Cox, Filipa; Robinson, Clare H.; Pittman, Jon K. (Frontiers in Plant Science, 2015)
Phytoaccumulation of radionuclides is of significant interest with regards to monitoring radionuclide build-up in food chains, developing methods for environmental bioremediation and for ecological management. There are many gaps in our understanding of the characteristics and mechanisms of plant radionuclide accumulation, including the importance of symbiotically-associated arbuscular mycorrhizal (AM) fungi. We first briefly review the evidence that demonstrates the ability of AM fungi to enhance the translocation of 238U into plant root tissues, and how fungal association may prevent further mobilization into shoot tissues. We then focus on approaches that should further advance our knowledge of AM fungi-plant radionuclide accumulation. Current research has mostly used artificial cultivation methods and we consider how more ecologically-relevant analysis might be performed. The use of synchrotron-based X-ray fluorescence imaging and absorption spectroscopy techniques to understand the mechanisms of radionuclide transfer from soil to plant via AM fungi is evaluated. Without such further knowledge, the behavior and mobilization of radionuclides cannot be accurately modelled and the potential risks cannot be accurately predicted.